A novel classical synthetic approach to carbon nanotubes and their functionalized derivatives - Wiredu, Bernard (Kansas State University, 2009)
Carbon nanotubes are allotropes of carbon comprising of one or more grapheme sheets seamlessly joined together to form a cylinder. They are classified as single-walled carbon nanotubes (SWNTs) or multi-walled carbon nanotubes (MWNTs). They have potential applications ranging from conductive and high reinforcement material components, nano interconnection in electronic devices to drug delivery in biological systems. Current methods of production are high temperature arc-discharge, laser ablation of graphitic materials and chemical vapor deposition. These methods give tubes that are impure and highly heterogeneous in length, diameter and chirality thus leading to mixture metallic and semiconducting tubes. Effective application of such carbon nanotubes requires cumbersome, harsh and expensive purification and sorting into like forms. Such treatments usually compromised the structural integrity of the tubes and hence their mechanical and electrical properties. Also pristine carbon nanotubes are insoluble in most solvents. Solubility in basic organic solvents is crucial prior to their application, which requires some level of chemical manipulation or functionalization on the tubes. Currently methods of functionalization are unpredictable and limited to few oxidation reactions. A novel rational synthetic chemical approach to [12, 12] arm-chair carbon nano tube with pre-defined diameter and length has been explored utilizing cheap and simple organic building blocks and results achieved so far have been presented in this dissertation. Two approaches were employed to form the carbon-rich beltene (32) before its final conversion to the target single-walled carbon nanotube (SWNT) 1. A survey on carbon nanotubes and their related structures including their potential applications and properties are presented in chapter 1. In the second chapter an iron template-assisted olefin metathesis via a ferrocene intermediate served as an anchor for an effective cyclization. In chapter 3, an un-assisted olefin metathesis pathway was explored. Both approaches use a series of benzyl halide carbonylation coupling and Diels-Alder reactions to synthesize some of the key intermediates. The protocol presented in this dissertation may be used to produce functionalized carbon nanotubes with predefined length and diameter tailored for specific applications to be produced in kilogram scale for the first time since its discovery in 1991. Such an approach is expected to address most if not all of the problems associated with the traditional methods of producing carbon nanotubes.
Keywords: Carbon nanotubes; Single-walled carbon nanotubes; Step-wise synthesis of carbon nanotubes; Functionalized derivatives of carbon nanotubes; Template-assisted olefin materials; Triphenylophane; Chemistry, General (0485); Chemistry, Organic (0490)